A study on the changes of the cell morphology, contents of pigments and intracellular protein in the life cycle of the green microalgal Haematococcus pluvialis under laboratory condition - Hoang, Dinh Duc; Tam, Luu Thi; Thu Thuy, Nguyen Thi; Hong, Dang Diem (Academia Journal of Biology, 2012)
The green unicellular algal Haematococcus pluvialis is a potential producer of astaxanthin, because it is capable of accumulating the highest proportion of astaxanthin around 5% of dry cell weight. In this report, a 50 days of model life cycle of the green algal H. pluvialis was constructed, consisting of four cell stages: 1. vegetative cell growth (prolong from 0 to 10 days of cultivation); 2. encystment (10-40 days of cultivation); 3. Maturation (40-50 days of cultivation); and 4. germination (within 2 days). Each algal cell stage could be distinguished each another by the profile of pigments and the intracellular protein content. During the life cycle of the algae, vegetative cells contained high levels of chlorophyll a and protein but they had very low carotenoid contents, whereas maturation of cyst cells was accompanied by enhancing carotenoid biosynthesis (especially astaxanthin) and accelerating protein degradation. The contents of chlorophyll a and astaxanthin tend to rise slowly in the first 20 days of cultivation, and then increased rapidly. After 40 days of cultivation, chlorophyll a content decreased whereas the content of astaxanthin is still increasing and reached maximal after 50 days of cultivation. The maximum astaxanthin content were 1424.23, 912.65 g/L and 1100, 800 g/L in media RM and C when culturing H. pluvialis in 250 and 500 ml flask, respectively. The highest cell diameter is around 40 m when cells of H. pluvialis were in maturation cell stage. Contrary to astaxathin and chlorophyll a contents, the content of intracellular protein tends to reduce when the cell began to convert from vegetative to cyst stage and accumulate astaxanthin. After 50 days of cultivation, protein content is less than 100 pg/cell which is decreased in 20 times compared with vegetative cell stage. In this study, we have determined astaxanthin/chlorophyll a ratio in each cell algal stage for distinguishing among vegetative, encyst, cyst and germination cells. Our obtained results have indicated that the astaxanthin/chlorophyll ratios were about 0.3 ± 0.05; 0.9 ± 0.20; 2.4 ± 0.10 and 0.60 ± 0.20 in vegetative, encyst, cyst and germination cell stages, respectively.